Ecotourism Governance Based on Community Participation - Rita Rahmawati (Indonesian Association for Public Administration (IAPA), 2020)
Sukagalih Village is one of the Conservation Village Models in the Mount Halimun Salak National Park area, which is a form of community participation in culture-based tourism management. Its location in the Mount Halimun Salak National Park area makes this location a potential ecotourism village. The purpose of this study was to determine the governance of Ecotourism Development based on community participation in Sukagalih Village. The research method used is descriptive with a qualitative approach. The data collection technique used interviews and participant observation. Based on the research results, the management of Sukagalih Ecotourism uses the CBE (community-based ecotourism) approach. The community-based ecotourism pattern recognizes the rights of local communities in managing tourism activities in areas they traditionally own or as managers. Through local institutions, the community is very actively involved in ecotourism management, namely through the provision of homestays for every tourist, community involvement through the management of outbound and camping ground. However, there are still various obstacles, so it still requires local government intervention to develop this ecotourism.